136k views
13 votes
Y=x^(2) -2x - 3 and y = x - 3

find the zeroes by solving the system of equations using the subsitution method

User Gsoni
by
4.7k points

1 Answer

8 votes

Answer:

(0, -3) and (3, 0)

Step-by-step explanation:

1st equation: y = x² -2x - 3

2nd equation : y = x - 3

Using substitution method:

x² -2x - 3 = x - 3 exchange sides

x² - 2x - x - 3 + 3 = 0 simplify

x² - 3x = 0 take common factor

x(x - 3) = 0 simplify

x = 0, 3

Solve for y:

when x is 0, y = x - 3 = 0 - 3 = -3

when x is 3, y = x - 3 = 3 - 3 = 0

User SanketS
by
4.9k points